2005
DOI: 10.1079/ber2005368
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical characterization of a sand fly population from Sri Lanka: evidence for insecticide resistance due to altered esterases and insensitive acetylcholinesterase

Abstract: With an increasing incidence of cutaneous leishmaniasis in Sri Lanka, particularly in northern provinces, insecticide-mediated vector control is under consideration. Optimizing such a strategy requires the characterization of sand fly populations in target areas with regard to species composition and extant resistance, among other parameters. Sand flies were collected by human bait and cattle-baited net traps on Delft Island, used as an illegal transit location by many refugees returning to the north of Sri La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 37 publications
1
62
0
1
Order By: Relevance
“…27 Sand fly behaviour has also been studied in the 1970's, 1990's and in 2005. 23,24,25,26 Both zoophilic and anthropophilic behaviour patterns have been identified in these studies.…”
Section: The Vector and Animal Reservoirsmentioning
confidence: 97%
See 1 more Smart Citation
“…27 Sand fly behaviour has also been studied in the 1970's, 1990's and in 2005. 23,24,25,26 Both zoophilic and anthropophilic behaviour patterns have been identified in these studies.…”
Section: The Vector and Animal Reservoirsmentioning
confidence: 97%
“…Sand fly research in Sri Lanka has a long history and the presence of sand flies has been reported since as early as the 1940's. 22,23,24 More recent information on Phlebotomine sand flies in Sri Lanka is available since 2005 25 where small numbers of Sergentomyia ceylanica were also identified. 26 Disregarding the negligible percentages of this species, P. argentipes could be the putative local vector of leishmaniasis in this country.…”
Section: The Vector and Animal Reservoirsmentioning
confidence: 99%
“…No obstante, Surendran et al (23) reportaron, en poblaciones de Phlebotomus argentipus de Egipto, que solamente en unos pocos individuos se detectó aumento de la actividad de GST y alteración de la AChe. Esto puede representar resistencia seleccionada por el rociamiento con malatión.…”
Section: Absorbanciasunclassified
“…AJ244359.1) (Surendran et al 2005). The sequence of Leishmania-specific PCR products were aligned and compared with the 18S rRNA sequence of L. donovani (GenBank accession no.…”
Section: Dna Sequencingmentioning
confidence: 99%
“…An initial denaturation of 15 min at 95°C, followed by PCR amplification for 35 cycles of denaturation (95°C for 30 sec), annealing (57°C for 30 sec), and polymerization (72°C for 40 sec), with final extension of 10 min at 72°C. To discriminate P. argentipes from other species, the amplified PCR product was subjected to restriction digestion using a Hae III restriction enzyme (recognition site GGCC; New England Bio Labs, Hitchin, Herts, U.K.) in the supplied reaction buffer supplemented with 1 mg/mL -1 BSA at 37°C for 2 h. The whole reaction was electrophoresed on a 1.5% (w/v) agarose gel and stained with ethidium bromide (Surendran et al 2005).…”
mentioning
confidence: 99%